Antiviral therapy reduces the risk of dementia in patients with herpes zoster: A propensity score‐matched analysis: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Bae, Sungman; Yoon, Woon; Choi, Seong Won; Yun, Sung‐Cheol; Kim, Sung‐han; Kim, Seong Yoon
Abstract: Background: Some epidemiological evidences show that the herpes zoster (HZ) may be associated with dementia. We investigated whether HZ was associated with the subsequent dementia in a nationwide population‐based (dynamic) cohort, and evaluated whether antiviral therapy might reduce the risk of subsequent dementia. Method: The National Health Insurance Service‐National Sample Cohort (NHIS‐NSC) database was used for analysis. This randomized one million people cohort representing the entire population of South Korea was followed up from 2002 to 2013. New events of HZ and dementia were identified using the diagnostic codes of claim data. Dementia was defined as the presence of the diagnostic codes and prescription of anti‐dementia drugs for more than 30 days. Each HZ patient receiving antiviral therapy was 1:1 matched with an untreated HZ patient having the same propensity score in the relevant year. Result: A total of 229, 594 individuals of ≥ 50 years were followed up for 11 years. The incidence of the first‐diagnosed HZ cases was 16.69 per 1000 person‐years, and that of the first‐diagnosed dementia was 4.67 per 1000 person‐years. The risk for dementia was higher in patients who had previous HZ episodes than in those who had never experienced HZ (incidence rate ratio [IRR] 1.94; 95% CI 1.83‐2.06 and adjusted hazard ratio [HR] 1.12; 95% CI 1.05‐1.19, respectively). Of the 34, 505 patients who were diagnosed as the first‐ever HZ, 28, 873 (84%) received antiviral treatment and 5, 632 (16%) did not. The crude incidence rates of the subsequent dementia were 7.79 and 12.27 per 1000 person‐years for treated and untreated groups, respectively, giving IRR of 0.63 (95% CI, 0.56‐0.72) and the covariate‐adjusted HR of 0.79 (95% CI, 0.69‐0.90). The HZ patients who received antiviral therapy had a significantly lower risk of dementia than those who did not; HR after propensity score‐matching was 0.77 (95% CI, 0.64‐0.91). In addition, the patients treated with antiviral agents showed significantly lower mortality than untreated patients (HR 0.58; 95% CI 0.53‐0.64 by propensity‐score matched analysis). Conclusion: HZ is associated with the subsequent dementia development, and the use of antiviral agents in patients with HZ significantly reduces the incidence of the subsequent dementia and the mortality.